2008
DOI: 10.1590/s1516-35982008000300003
|View full text |Cite
|
Sign up to set email alerts
|

Produção de massa seca, relação folha/colmo e alguns índices de crescimento do Brachiaria brizantha cv. Xaraés cultivado com a combinação de doses de nitrogênio e potássio

Abstract: RESUMO -Objetivou-se avaliar a produção de massa seca das folhas, a relação folha/colmo e alguns índices de crescimento do capim-xaraés submetido a doses de nitrogênio (N) e potássio (K). O experimento foi conduzido em casa-de-vegetação no período de novembro/2004 a fevereiro/2005. Adotou-se esquema fatorial 4 × 3, perfazendo 12 combinações, as quais foram distribuídas em delineamento experimental inteiramente casualizado, com quatro repetições, perfazendo um total 48 unidades experimentais. Foram utilizadas q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0
40

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 4 publications
3
20
0
40
Order By: Relevance
“…Estudos de produção de massa seca de folhas em gramíneas forrageiras são importantes em razão das folhas se constituírem no órgão das plantas preferencialmente consumidas pelos animais além de ser a principal fonte de nutrientes para os ruminantes em sistema de pastejo (Rodrigues et al, 2008).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Estudos de produção de massa seca de folhas em gramíneas forrageiras são importantes em razão das folhas se constituírem no órgão das plantas preferencialmente consumidas pelos animais além de ser a principal fonte de nutrientes para os ruminantes em sistema de pastejo (Rodrigues et al, 2008).…”
Section: Resultsunclassified
“…Segundo Rodrigues et al (2008) no desenvolvimento inicial das Tabela 4. Relação MSF/MSC no primeiro e no terceiro corte das cultivares de Brachiaria brizantha sob diferentes disponibilidades hídricas do solo gramíneas forrageiras a produção de massa seca é composta basicamente de folhas.…”
Section: Resultsunclassified
“…Thus, the plant shall reallocate the photo-assimilated compounds of the roots to form the new shoot, a fact that has been evident in this study, where the grass under conditions of adequate moisture and fertilizer had as impediment to its development just the barrier imposed by the layer of compacted soil under the root system. RODRIGUES et al (2008) affirm that there is variation in the source/drain relation, in which the plant directs the energy of production of the shoot for the formation of its root system. FREDDI et al (2007), studying soil compaction on root growth and productivity of maize crop, also reported an increase in density and root surface in the layer from 0 to 10 cm with the increase of compaction.…”
Section: Resultsmentioning
confidence: 90%
“…Confronting the works of Rodrigues et al (2008), Teles et al (2011) and Sales et al (2013) showed that the Brachiaria brizantha cultivars have different behavior regarding the management of fertilization, being important to consider the peculiarities of each cultivar in its management.…”
Section: Resultsmentioning
confidence: 99%
“…by several authors, such as Mistura et al (2006), working with Elephant grass (Pennisetum purpureum Schum. ), and Lavres Júnior & Monteiro (2002) and Rodrigues et al (2008), researching the Xaraés grass (Brachiaria brizantha).…”
Section: Resultsmentioning
confidence: 99%